EHRLICHIOSIS AND DEMODICOSIS IN BALI LOCAL DOG - Muhammad Farhan Al Ma’arif; Putu Devi Jayanti; I Gede Soma (Buletin Veteriner Udayana, 2024)
Ehrlichiosis is a zoonotic disease caused by infection with intracellular bacteria Ehrlichia sp. which can be transmitted by ticks. Demodicosis is a parasitic disease caused by the mite Demodex sp. which has a predilection for the dermis, hair follicles, and sebaceous glands. A male local breed dog aged approximately 2 years with a body weight of 8 kg came with complaints of hair loss and high intensity itching with a scale of 8/10. The results of clinical examination showed alopecia, scale, and erythema almost all over the body accompanied by tick infestations found on the back, anemic mucosa, left prescapularis lymph nodes and left popliteus experienced swelling. Hematological examination showed macrocytic hypochromic anemia, leukocytosis, lymphocytosis, granulocytosis, and thrombocytopenia. Blood smear and serology examination showed Ehrlichia sp.. infection while deep skin scrapping examination showed Demodex sp. infection. Based on the anamnesis, physical examination and laboratory examination, the case of the dog suffering from ehrlichiosis accompanied by demodecosis. The therapy given was in the form of doxycycline, ivermectin, diphenydramine, vitamin B complex, and bath therapy with sulfur soap. Observation of therapy on the 14th day provided clinical improvement in terms of reducing itching intensity, Demodex sp. infection intensity, and hematological parameters. On the 28th day of the last treatment, the dog's body condition was getting better, new hair started to grow and the body condition score increased. Dogs should be given food rich in nutrients such as liver, meat and egg yolks, as well as providing nutritional supplements to speed up the dog's recovery.